Status of Sarawak fisheries : challenges and way forward / Wen Chiat Lee ... [et al.] - Wen, Chiat Lee; Viswanathan, K. Kuperan; Kamri, Thalany; Siew, King Ting (Universiti Teknologi MARA Cawangan Sarawak, 2020)
Fisheries are important to Sarawak's economy. Fisheries provide job opportunities and income to the people besides contributing to Sarawak's gross domestic product. Sarawak's fisheries can be divided into marine capture fisheries and aquaculture. In this paper, we discuss the status of Sarawak fisheries. Moreover, challenges of fisheries in Sarawak are also discussed. The major challenges are encroachment by illegal fishers and poor institutional organizations of fishers, and more recently, the impact of Covid-19 on Sarawak's fisheries. There are three suggestions for sustainable fisheries development in Sarawak. Firstly, the control of illegal and undocumented fishing; secondly, the transformation of fishermen associations into functioning cooperatives to improve welfare and livelihood of fishers; and thirdly, the development of aquaculture to augment fisheries production and increase the income of fishers and rural people.